1996
DOI: 10.1007/bf00010993
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil compaction on growth and P uptake by Trifolium subterraneum: interactions with mycorrhizal colonisation

Abstract: The effects of vesicular-arbuscular mycorrhizal (VAM) colonisation on phosphorus (P) uptake and growth of clover (Trifolium subterraneum L.) in response to soil compaction were studied in three pot experiments. P uptake and growth of the plants decreased as the bulk density of the soil increased from 1.0 to 1.6 Mg m -3. The strongest effects of soil compaction on P uptake and plant growth were observed at the highest P application (60 mg kg-1 soil). The main observation of this study was that at low P applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
7

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 36 publications
5
42
0
7
Order By: Relevance
“…Barker plants were grown in autoclaved soil collected from a Mediterranean type Eucalyptus forest (Waite Hill Face Reserve, Adelaide, Australia) with a very low extractable P concentration (Colwell, 1963), 6 µg −" of NaHCO $ extractable P and a neutral pH (pH 6.4 in 10 mM CaCl # ). This concentration of available P has been reported to limit growth of T. subterraneum in previous pot experiments (Nadian et al, 1996). Autoclaving this soil had no toxic effect on T. subterraneum (E. Facelli, unpublished data).…”
Section: Effects Of Mycorrhizas and Densitymentioning
confidence: 51%
See 1 more Smart Citation
“…Barker plants were grown in autoclaved soil collected from a Mediterranean type Eucalyptus forest (Waite Hill Face Reserve, Adelaide, Australia) with a very low extractable P concentration (Colwell, 1963), 6 µg −" of NaHCO $ extractable P and a neutral pH (pH 6.4 in 10 mM CaCl # ). This concentration of available P has been reported to limit growth of T. subterraneum in previous pot experiments (Nadian et al, 1996). Autoclaving this soil had no toxic effect on T. subterraneum (E. Facelli, unpublished data).…”
Section: Effects Of Mycorrhizas and Densitymentioning
confidence: 51%
“…We selected T. subterraneum as the host because the response of single plants of this species to mycorrhizal infection under different concentrations of P and light intensities has been studied in detail (Smith, 1982 ;Tester et al, 1985Tester et al, , 1986Nadian et al, 1996).…”
Section: mentioning
confidence: 99%
“…Nadian et al (1996) showed that the mycorrhizal growth response, the effect of AM fungi on P uptake and growth of the host plant, decreased as the bulk density of the soil increased. Compacted soil decreased the percentage of large (> 30 fJ.-m) soil pores (Nadian et al 1996) and inhibited the elongation of the roots (Nadian et al 1996;Yano et al 1998) and also hyphae of the AM fungi (E. Drew, personal communication). In this study, soil compaction might occur in the absence of the soil amendments and suppress mycorrhizal function as a P supplier.…”
Section: Resultsmentioning
confidence: 99%
“…These values lie within the range previously reported. Estimates of hyphal P inflow vary considerably, ranging from 1-19i10 −"$ mol m −" (root) s −" (Jakobsen et al, 1992a) to 238i10 −"$ mol m −" (root) s −" (Nadian, 1998). Apart from uncertainty about the assumptions behind the calculations, these values are of course influenced by many factors, including levels of soil P, the fungal isolates, host plants and soil used, production of external hyphae, extent of colonization, and the time period used for the calculation.…”
Section: mentioning
confidence: 99%